Passing through the filter - Nijolė Maskaliūnienė; Gintarė Juršėnaitė (Stridon, 2023)
This article presents the translations of Spanish and Latin American authors into Lithuanian during the 50 years of Soviet occupation (1940–1990). The purpose of this research is to explore the legacy of these translations within the context of preventive censorship practiced in the Soviet Union. Preventive censorship involves selectively filtering books and authors for inclusion or exclusion from publication due to ideological or political considerations (cf. Leonardi 2008). The article addresses three main questions: (1) What was the volume of Spanish-language literature in the overall corpus of translations in Soviet Lithuania? (2) Which Spanish-language authors were accessible to Lithuanian readers during the period under consideration? And (3) What factors might have influenced their selection for publication in Lithuanian translation? An attempt is made to describe the corpus of translations from Spanish into Lithuanian, with a particular focus on the selection criteria to be met for inclusion of these literary works in the Soviet canon of foreign literature.